The global and regional costs of healthy and sustainable dietary patterns: a modelling study. Issue 11 (November 2021) - Springmann, Marco; Clark, Michael A; Rayner, Mike; Scarborough, Peter; Webb, Patrick
Summary: Background: Adoption of healthy and sustainable diets could be essential for safe-guarding the Earth's natural resources and reducing diet-related mortality, but their adoption could be hampered if such diets proved to be more expensive and unaffordable for some populations. Therefore, we aimed to estimate the costs of healthy and sustainable diets around the world. Methods: In this modelling study, we used regionally comparable food prices from the International Comparison Program for 150 countries. We paired those prices with estimates of food demand for different dietary patterns that, in modelling studies, have been associated with reductions in premature mortality and environmental resource demand, including nutritionally balanced flexitarian, pescatarian, vegetarian, and vegan diets. We used estimates of food waste and projections of food demand and prices to specify food system and socioeconomic change scenarios up to 2050. In the full cost accounting, we estimated diet-related health-care costs by pairing a comparative risk assessment of dietary risks with cost-of-illness estimates, and we estimated climate change costs by pairing the diet scenarios with greenhouse gas emission footprints and estimates of the social cost of carbon. Findings: Compared with the cost of current diets, the healthy and sustainable dietary patterns were, depending on the pattern, up to 22–34% lower in cost in upper-middle-income to high-income countries on average (when considering statistical means), but at least 18–29% more expensive in lower-middle-income to low-income countries. Reductions in food waste, a favourable socioeconomic development scenario, and a fuller cost accounting that included the diet-related costs of climate change and health care in the cost of diets increased the affordability of the dietary patterns in our future projections. When these measures were combined, the healthy and sustainable dietary patterns were up to 25–29% lower in cost in low-income to lower-middle-income countries, and up to 37% lower in cost on average, for the year 2050. Variants of vegetarian and vegan dietary patterns were generally most affordable, and pescatarian diets were least affordable. Interpretation: In high-income and upper-middle-income countries, dietary change interventions that incentivise adoption of healthy and sustainable diets can help consumers in those countries reduce costs while, at the same time, contribute to fulfilling national climate change commitments and reduce public health spending. In low-income and lower-middle-income countries, healthy and sustainable diets are substantially less costly than western diets and can also be cost-competitive in the medium-to-long term, subject to beneficial socioeconomic development and reductions in food waste. A fuller accounting of the costs of diets would make healthy and sustainable diets the least costly option in most countries in the future. Funding: Global Panel on Agriculture and Food Systems for Nutrition and Wellcome Trust.